A Kvisoft Flipbook Maker-Assisted E-Book to Increase Students' Interest In Elementary Schools - Amanda Hiralda; Zulherman (Jurnal Ilmiah Sekolah Dasar, 2023)
Students' interest in studying science subjects with material on Earth and the Universe in sixth class is still low. It is caused by various factors, one of which is the media of teaching materials that are still conventional. This research aims to develop media in ebooks assisted by Kvisoft Flipbook Maker. This research uses the R&D (Research and Development) method with the ADDIE model. The research subjects consisted of material validators, media validators, language validators, and 62 class VI students. Data collection techniques in this study using observation and tests. The instrument used in this study was a questionnaire given to the validator and a pretest and posttest given to students. Data analysis was carried out in a quantitative descriptive manner. The results of the research are the validation of media experts in a 92% very feasible category, material experts in a 99% very feasible category, and linguists in an 86.15% very feasible category. The results showed that ebook development was very good, so there was an increase in learning outcomes with ebook teaching materials assisted by Kvisoft Flipbook Maker. This research proves that this research contributes to increasing the interest of elementary school students.